EFFICIENCY OF MORINGA OLEIFERA AS A NATURAL COAGULATION AND FILTRATION AGENT FOR REMOVAL OF MINERALS FROM HARD WATER: AN IN-DEPTH ANALYSIS OF MOLECULAR MECHANISMS, ADSORPTION KINETICS, AND TECHNO-ECONOMIC FEASIBILITY - Rawell, Mayane (Journal of Interdisciplinary Debates, 2025)
The increasing demand for drinking water and the environmental impacts associated with conventional chemical treatments have driven research into clean and sustainable technologies. Water hardness, caused primarily by calcium ions (Ca²+) and magnesium (Mg²+), poses a significant challenge in domestic and industrial contexts. This study evaluates, through an in-depth literature review and a detailed proposal of an experimental model, the efficiency of Moringa oleifera (MO) as a natural coagulant and filtration agent for the removal of mineral ions (Ca²+, Mg²+, Fe²+/Fe3+, Zn²+ ) from hard water. The proposed methodology involves the development of a hybrid gravitational filtration system composed of activated carbon beds with controlled particle size and the application of coagulant based on OM seeds. The analysis of previous studies indicates that the cationic proteins present in OM seeds, with molecular weights between 6.5 and 48 kDa and isoelectric point above pH 10, they act effectively through adsorption mechanisms (Langmuir and Freundlich isotherms), neutralization of charge and precipitation, promoting agglutination and subsequent removal of dissolved particles and ions. The literature reports turbidity removal rates of more than 99%, pathogenic microorganisms (> log 6 for E. coli) and metals such as iron up to 100%. Kinetic studies demonstrate that the adsorption process follows pseudo-second-order models, indicating chemisorption as the predominant mechanism. Comparative economic analysis reveals that the costs of treatment with OM can be up to 50% lower than those of aluminum sulfate in rural contexts. Based on these data, it is projected that the proposed biotechnological system will achieve mineral removal efficiencies greater than 95%, consolidating itself as a low-cost, ecologically viable and high-performance alternative for hard water treatment, applicable at various scales and socioeconomic contexts.